2020
DOI: 10.1021/acs.jctc.0c00037
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Mechanisms in Temperature Dependence of DNA Double Helical Structure: Bending and Elongation

Abstract: Changes in the structure of double-stranded (ds) DNA with temperature affect processes in thermophilic organisms and are important for nanotechnological applications. Here we investigate temperature-dependent conformational changes of dsDNA at the scale of several helical turns and at the base pair step level, inferred from extensive all-atom molecular dynamics simulations of DNA at temperatures from 7 to 47 °C. Our results suggest that, contrary to twist, the overall bending of dsDNA without A-tracts depends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 28 publications
3
33
0
Order By: Relevance
“…Helix narrowing is absorbed by an increase in helicity (i.e., decrease of crookedness), an increase of the sugar pucker angle (Figure 3d, e) and a small decrease of the helical rise (Figure 3b). These changes are identical to the known overwinding compensatory mechanism of DNA 33 and result in increasing DNA twist with increasing salt concentration.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Helix narrowing is absorbed by an increase in helicity (i.e., decrease of crookedness), an increase of the sugar pucker angle (Figure 3d, e) and a small decrease of the helical rise (Figure 3b). These changes are identical to the known overwinding compensatory mechanism of DNA 33 and result in increasing DNA twist with increasing salt concentration.…”
supporting
confidence: 61%
“…MD simulations are highly complementary to MT measurements, as they provide detailed, microscopic insights by resolving ionnucleic acid interactions and the resulting conformational changes with atomistic resolution. 9,12,13,[31][32][33][34][35] The resolution afforded by MD simulations [36][37][38][39] allows us to disentangle the contributions of backbone, nucleobases, ions, and water, which, in turn, provide a comprehensive view of the origin of ion specificity in DNA twist. Conversely, high-resolution twist measurements provide a useful test for current MD simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12,27,29 Highly soft stretch modulus measured by SAXS experiments on short oligomers 31 was observed to be caused mainly by end effects. 27 For the persistence length, we found that the periodic tangent-tangent correlation reflected the ''crookedness'' 32 of the static curvature of the DNA helix 26,27,29,30,[32][33][34][35] and, without considering these modulations, the decay was close to the consensus value of 50 nm. [6][7][8][9][10] Thus, the LDEM is suitable for describing the average mechanical properties of DNA and, from this perspective, it was applied to test the DNA force-field for atomic simulations, Parmbsc1.…”
Section: Introductionmentioning
confidence: 76%
“…However, further research is needed to better characterize the DNA A-philicity, crookedness and stretching flexibility, in order to establish a more solid connection between these DNA features. Along this line, a recent study by Lankas and coworkers has expanded our understanding on DNA crookedness, by assessing how this parameter depends on the temperature of the system (Dohnalová et al ., 2020).…”
Section: Sequence-dependent Dna Mechanicsmentioning
confidence: 99%